Prevalence and severity of plaque-induced gingivitis in three Latin American cities : Mexico City-Mexico, Great Metropolitan Area-Costa Rica and Bogota-Colombia = Prevalencia y severidad de gingivitis inducida por placa en tres ciudades de Latinoamérica: Ciudad de México-México, Gran Área Metropolitana-Costa Rica y Bogotá- Colombia - Murillo Knudsen, Gina 1959-; Vargas, Maria Alejandra; Castillo Rivas, Salvadora Jacqueline 1964-; Serrano Alvarez, Juan Jaime; Ramirez, Gloria Marcela (2018)
Plaque-induced gingivitis is the most common form of periodontal disease and can affect 100% of the population. Gingivitis prevalence in Latin American population is not well documented, therefore the aim of this study was to determine the prevalence and severity of plaque-induced gingivitis in adult populations of three Latin American cities. Methods: This cross sectional multicenter study included 1650 participants, 550 from the Great Metropolitan Area of Costa Rica (GAM), 550 from Mexico City, Mexico (CDMX) and 550 from Bogota City, Colombia (BC). Subjects completed a questionnaire about their medical history and oral hygiene. Clinical assessment included recording of missing teeth, visible plaque index, calculus recording and gingival index (GI, Loe-Silness index). Results: Average GI was 1.36. No statistical difference was found between GAM (1.45) and BC (1.48); however, GI in CDMX was significantly lower (1.16). Average gingival bleeding on probing was 43%. Total plaque index was 0.76 showing the highest accumulation at interproximal sites (p=0.0001). A positive correlation was found between plaque and gingivitis (r=0.59). Dental calculus was present in at least one of the 18 evaluated sites per subject with no statistical difference between cities. There was no statistical difference in GI between smokers, former smokers and non- smokers. Conclusion: Gingivitis prevalence was 99.6%. Moderate Gingivitis was the predominant form, with no statistically significant difference between cities or gender. Dental plaque accumulation was the most important risk factor associated with the establishment of the disease.
La gingivitis inducida por placa es la forma más común de enfermedad periodontal y puede afectar al 100% de la población. La prevalencia de gingivitis en Latinoamerica no está bien documentada, por lo tanto, el objetivo de este estudio fue determinar la prevalencia y severidad de la gingivitis inducida por placa en poblaciones adultas de tres ciudades latinamericanas. Metodología: Este estudio transversal multicéntrico incluyó 1650 sujetos, 550 del Gran Área Metropolitana de Costa Rica (GAM), 550 de la Ciudad de México, México (CDMX) y 550 de la Ciudad de Bogotá, Colombia (BC). Los sujetos completaron un cuestionario sobre su historia médica y hábitos de higiene oral. El examen clínico incluyó el registro de piezas dentales ausentes, el índice de placa visible, el registro de cálculo y el índice gingival (GI, Índice de Silness y Loe). Resultados: El GI promedio fue de 1.36. No se encontró diferencia estadísticamente significativa entre GAM (1.45) y BC (1.48); sin embargo, el índice gingival en CDMX fue menor (1.16). El promedio de sangrado al sondaje fue de 43%. El índice de placa total fue 0.76, mostrando la mayor acumulación en sitios interproximales (p=0.0001). Se encontró una correlación positiva entre placa y gingivitis (r=0.59). Hubo presencia de cálculo dental en al menos uno de los 18 sitios evaluados por cada sujeto sin diferencia estadística entre ciudades. No se encontró diferencia estadísticamente significativa en cuanto al índice gingival entre fumadores, ex fumadores y no fumadores. Conclusión: La prevalencia de Gingivitis fue del 99.6%. La Gingivitis Moderada fue la forma predominante, sin diferencia estadísticamente significativa por ciudad o sexo. La acumulación de placa fue el principal factor de riesgo asociado con el establecimiento de la enfermedad.
En revista Odóvtos, vol. 20, no. 2 (mayo-agosto 2018)
Descripción basada en el contenido visto 23 de julio, 2024
También disponible en formato HTML
Keywords: SALUD ORAL; GINGIVITIS; PLACA DENTAL; AMERICA LATINA